APOE ε4 and exercise interact in a sex‐specific manner to modulate dementia risk factors. Issue 1 (29th June 2022) - Foley, Kate E.; Diemler, Cory A.; Hewes, Amanda A.; Garceau, Dylan T.; Sasner, Michael; Howell, Gareth R.
Abstract: Introduction: Apolipoprotein E ( APOE ) ε4 is the strongest genetic risk factor for Alzheimer's disease and related dementias (ADRDs), affecting many different pathways that lead to cognitive decline. Exercise is one of the most widely proposed prevention and intervention strategies to mitigate risk and symptomology of ADRDs. Importantly, exercise and APOE ε4 affect similar processes in the body and brain. While both APOE ε4 and exercise have been studied extensively, their interactive effects are not well understood. Methods: To address this, male and female APOE ε3/ε3, APOE ε3/ε4, and APOE ε4/ε4 mice ran voluntarily from wean (1 month) to midlife (12 months). Longitudinal and cross‐sectional phenotyping were performed on the periphery and the brain, assessing markers of risk for dementia such as weight, body composition, circulating cholesterol composition, murine daily activities, energy expenditure, and cortical and hippocampal transcriptional profiling. Results: Data revealed chronic running decreased age‐dependent weight gain, lean and fat mass, and serum low‐density lipoprotein concentration dependent on APOE genotype. Additionally, murine daily activities and energy expenditure were significantly influenced by an interaction between APOE genotype and running in both sexes. Transcriptional profiling of the cortex and hippocampus predicted that APOE genotype and running interact to affect numerous biological processes including vascular integrity, synaptic/neuronal health, cell motility, and mitochondrial metabolism, in a sex‐specific manner. Discussion: These data in humanized mouse models provide compelling evidence that APOE genotype should be considered for population‐based strategies that incorporate exercise to prevent ADRDs and other APOE ‐relevant diseases.